2018
DOI: 10.1186/s13052-018-0496-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of electrolyte disturbances in perinatal asphyxia: a prospective study

Abstract: BackgroundBirth asphyxia is defined as the presence of hypoxia, hypercapnia, and acidosis leading the newborn to systemic disturbances probably electrolyte disturbance also. Knowledge of these electrolyte disturbances is very valuable as it can be an important parameter affecting perinatal morbidity, mortality and ongoing management.MethodsSerum sodium, potassium and ionized calcium of asphyxiated term newborn were sent within one hour of birth as per the inclusion criteria. Statistical comparison of mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 17 publications
6
20
1
1
Order By: Relevance
“…Other associated factors like breech presentation, macrosomia, and large size baby increase the severity of birth asphyxia. Previous studies in other parts of India and developing countries had similar findings [11,16]. Our study revealed that forceps/ventouse delivery may lead to severe birth asphyxia (p < 0.01), whereas LSCS is better and associated with HIE I (p < 0.001).…”
Section: Figure 1: Line Diagram Showing the Mean Serum Sodium (Na+) Asupporting
confidence: 86%
See 1 more Smart Citation
“…Other associated factors like breech presentation, macrosomia, and large size baby increase the severity of birth asphyxia. Previous studies in other parts of India and developing countries had similar findings [11,16]. Our study revealed that forceps/ventouse delivery may lead to severe birth asphyxia (p < 0.01), whereas LSCS is better and associated with HIE I (p < 0.001).…”
Section: Figure 1: Line Diagram Showing the Mean Serum Sodium (Na+) Asupporting
confidence: 86%
“…Thus, the sodium reabsorption capacity of the direct Coombs test (DCT) and more sodium loss in the urine causes hyponatremia. Further, birth asphyxia causes a syndrome of inappropriate antidiuretic hormone secretion (SIADH) and partial aldosterone resistance, leading to hyponatremia [ 16 ]. Hyponatremia leads to hypovolemia and further compromise of renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…The result was in concordance with those of Basu et al 15 This lowered serum sodium (hyponatremia) which developed perinatally, proportionally contributes to the development of more severe asphyxia if not rectified immediately. 16 The serum potassium level among asphyxiated neonates was significantly higher than that of the controls. This increase in the serum potassium (hyperkaliemia) among the asphyxiated neonates showed a negative correlation with the Apgar score.…”
Section: Discussionmentioning
confidence: 82%
“…Thakur et al have investigated electrolyte (sodium, potassium, calcium) disturbances in asphyxiated newborns of different severity [102]. They found that hyponatremia, hyperkalemia and hypocalcemia occurring in neonates with perinatal asphyxia may be responsible for increased morbidity and mortality and that hyponatremia and hyperkalemia are positively associated with the severity of birth asphyxia, thus confirming the data from Basu et al [103].…”
Section: Reviewmentioning
confidence: 58%